Social Work in Germany - Hopmann, Benedikt; Schmitt, Caroline; Witte, Matthias D. (Pedagogika Społeczna Nova, 2023)
Social Work in Germany developed out of the tradition of assistance for the poor and the youth movement. The two historical fields of social work (Sozialarbeit) and Social Pedagogy (Sozialpädagogik) overlap, and in this contribution they are united under the heading of Social Work (Soziale Arbeit). This contribution offers insights into the historical emergence of Social Work in Germany, its organisational structures, its working methods and the current debate on how to make the German welfare system inclusive. This fundamental structural change is an invitation to the infrastructures of Social Work to undertake critical re-assessment and reflection. The contribution concludes with some ideas on what Social Work could be like if it is led by critical reflection, is self-confident, constantly scrutinises the directions it is taking in the light of its aspiration to produce inclusion and promote autonomy, and if its national and international organisations and global expertise are even more united than before.